A Confusing Coincidence: Neonatal Hypoglycemic Seizures and Hyperekplexia - Nihat Demir; Murat Doğan; Sanem Yılmaz; Erdal Peker; Keziban Bulan; Oğuz Tuncer (Case Reports in Medicine)
Hyperekplexia is a rare, nonepileptic, genetic, or sporadic neurologic disorder characterized by startle responses to acoustic, optic, or tactile stimuli. Genetic defects in glycine receptors as well as encephalitis, tumors, inflammation, and disgenesis are among the etiologic causes of the disease. The main problem in hyperekplexia is the incomplete development of inhibitory mechanisms or exaggerated stimulation of excitatory mediators. Hyperekplexia is often confused with epileptic seizures. Here we present a case with hypoglycemic convulsions coexisting with hyperekplexia, causing diagnostic difficulty.